2013
DOI: 10.1177/1059840513480815
|View full text |Cite
|
Sign up to set email alerts
|

Body Art Education

Abstract: Using the major format identified for successful prevention and intervention work, five "W" questions: what, why, whom, where, and who, plus one: how, this article first summarizes the current body art literature. Then, educational strategies specifically regarding the topic of tattoos and body piercing are presented for school nurses. These strategies can be used to create applicable, realistic information for young students before they are faced with decisions related to body art. The school nurse might be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Body piercing has become very popular in the past two decades, and it has been reported that approximately 50% of millennials receive at least one non-earlobe piercing [ 1 , 2 ]. As most of these piercings are not performed in clinical settings, 17–46% of the piercings lead to complications [ 3 , 4 ] including infection, metal allergy, bleeding, and tissue scarring [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body piercing has become very popular in the past two decades, and it has been reported that approximately 50% of millennials receive at least one non-earlobe piercing [ 1 , 2 ]. As most of these piercings are not performed in clinical settings, 17–46% of the piercings lead to complications [ 3 , 4 ] including infection, metal allergy, bleeding, and tissue scarring [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%